GE_GERICHTE A/2049/2005 vom 2. November 2005 - GE Cour de justice (2005)
; CHÔMAGE ; CONDITION DU DROIT À LA PRESTATION D'ASSURANCE ; DOMICILE ; DOMICILE À L'ÉTRANGER ; INTENTION DE S'ÉTABLIR ; CENTRE DE VIE | LACI.8.1.let.c; CC.23